Dose-response of diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] in the urothelial mucosa of Wistar rats - Cardoso, Ana Paula Ferragut [UNESP]; Ihlaseh Catalano, Shadia Muhammad [UNESP]; da Rocha, Mitscheli Sanches [UNESP]; Nascimento e Pontes, Merielen Garcia [UNESP]; Camargo, João Lauro Viana de [UNESP]; Oliveira, Maria Luiza Cotrim Sartor de [UNESP] (Elsevier, 2013)
Diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] is a herbicide that induced urothelial tumors in the urinary bladder of Wistar rats fed 2500. ppm during a long-term study. The currently suggested non-genotoxic mode of action (MOA) of diuron encompasses in succession urothelial necrosis induced by direct cytotoxicity, regenerative cell proliferation and sustained urothelial hyperplasia that increases the likelihood of neoplasia development. This study evaluated the dose-response profile of urothelial histological and ultrastructural lesions induced by diuron. Sixty male Wistar rats were fed ad libitum diuron mixed in the diet at 0, 60, 125, 500, 1250, or 2500. ppm for 20 weeks. The incidences of urothelial simple hyperplasia and the cell proliferation index were significantly increased in the diuron-fed 1250 and 2500. ppm groups. By scanning electron microscopy, the incidences and severity of lesions were significantly increased in the 500 and 1250. ppm groups. The incidences of urothelial hyperplasia in the kidney pelvis were significantly increased in the 500, 1250 and 2500. ppm groups. The present study documents the dose-response influence of diuron on the rat urothelium, with a no observed effect level (NOEL) at 125. ppm; 1250. ppm was as effective as 2500. ppm at inducing urothelial lesions. © 2013 Elsevier B.V.
Keywords: Cell proliferation; Cytotoxicity; Diuron; Dose-response; Rat urothelial hyperplasia; Scanning electron microscopy; diuron; animal tissue; cell proliferation; controlled study; diet; dose response; histopathology; hyperplasia; kidney pelvis; male; mucosa; nonhuman; priority journal; rat; scanning electron microscopy; urothelium; weight gain